Sustainability of horticultural farming in Purbalingga Regency: an empirical analysis using multidimensional scaling - Sodik Dwi Purnomo; Damar Jati; Alfit Budi Prasetyo; Tri Esti Masita; Heru Cahyo; Noviati Aning Rizki Mustika Sari; Mutia Pamikatsih (Journal of Agricultural Socio-Economics (JASE), 2026)
Horticultural crops are important commodities for supporting food needs and local economic development in Karangreja District, Purbalingga Regency. However, limited land availability, declining productivity, low farmer education, climate change, and pest attacks pose significant challenges to achieving sustainable farming. Unlike previous studies, which generally assess farming sustainability across ecological, economic, and social dimensions, this study integrates technological and institutional dimensions to provide a more comprehensive assessment. This study aims to assess the sustainability status of horticultural farming in Karangreja District across five dimensions: ecological, economic, social, technological, and institutional. A total of 97 farmers were selected as respondents through purposive sampling, and the data were analyzed using Multidimensional Scaling. The results show that overall sustainability falls into the moderately sustainable category, with an index value of 53.38. The ecological, economic, technological, and institutional dimensions are classified as moderately sustainable, with index values of 58.71, 54.72, 51.48, and 62.07, respectively. In contrast, the social dimension is classified as less sustainable, with the lowest index value of 39.93. These findings indicate that the sustainability of horticultural farming is relatively maintained but remains vulnerable in the social dimension. Therefore, policy interventions should prioritize farmer education, youth farmer regeneration, extension services, and institutional support to improve the long-term sustainability of horticultural farming.